2008
DOI: 10.1073/pnas.0810246105
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors reverse type 1 diabetes in nonobese diabetic mice

Abstract: The recent development of small-molecule tyrosine kinase (TK) inhibitors offers increasing opportunities for the treatment of autoimmune diseases. In this study, we investigated the potential of this new class of drugs to treat and cure type 1 diabetes (T1D) in the NOD mouse. Treatment of prediabetic and new onset diabetic mice with imatinib (Gleevec) prevented and reversed T1D. Similar results were observed with sunitinib (Sutent), an additional approved multikinase inhibitor, suggesting that the primary targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(200 citation statements)
references
References 51 publications
(59 reference statements)
6
191
2
1
Order By: Relevance
“…In streptozotocin-induced and spontaneous (non-obese diabetic and db/db) mouse models of diabetes, imatinib has been shown to preserve islet b-cell function, in part through the suppression of c-abl-mediated islet cell apoptosis (Hagerkvist et al 2007, Han et al 2009). Imatinib and other inhibitors of PDGFR have also been shown to prevent and even reverse diabetes in nonobese diabetic mice through a mechanism that may involve suppression of a PDGF-induced inflammatory response (Louvet et al 2008). More recently, we have demonstrated that plasma levels of an adipokine, adiponectin, are elevated two-to three-fold in CML patients after 3 months of imatinib therapy .…”
Section: Introductionmentioning
confidence: 65%
“…In streptozotocin-induced and spontaneous (non-obese diabetic and db/db) mouse models of diabetes, imatinib has been shown to preserve islet b-cell function, in part through the suppression of c-abl-mediated islet cell apoptosis (Hagerkvist et al 2007, Han et al 2009). Imatinib and other inhibitors of PDGFR have also been shown to prevent and even reverse diabetes in nonobese diabetic mice through a mechanism that may involve suppression of a PDGF-induced inflammatory response (Louvet et al 2008). More recently, we have demonstrated that plasma levels of an adipokine, adiponectin, are elevated two-to three-fold in CML patients after 3 months of imatinib therapy .…”
Section: Introductionmentioning
confidence: 65%
“…The complex of c-Abl⅐Prdx1 is thought to be a major target of oxidative stress and has been shown to play an important role in the pathogenesis of vascular disease, such as atherosclerosis and diabetes mellitus (43)(44)(45)(46) as well as cancer and other agingrelated diseases such as osteoporosis (47). Further study using disease-model animal is required to elucidate the significance of protective role of AMPK on c-Abl⅐Prdx1 complex in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the inhibition of plateletderived growth factor receptor by sunitinib can promote pancreatic β-cell survival [Mokhtari and Welsh, 2010], sunitinib treatment may be suitable for patients with glucagonoma but may have detrimental effects on patients with insulinoma. Preclinical studies have shown sunitinib to, in fact, reverse type 1 diabetes [Louvet et al 2008]. In a patient with metastatic renal cell carcinoma, however, sunitinib treatment induced long-term remission from recent-onset type 1 diabetes mellitus [Templeton et al 2008].…”
Section: Use In Specific Patient Populationsmentioning
confidence: 99%